GPS-Tracking in touristischen Destinationen – Neue Software-Anwendung zur Erfassung des Mobilitätsverhaltens am Beispiel von Wanderern im Harz - Groß, Sven; Menzel, Anne (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
There is a variety of quantitative and qualitative methods available to analyze the mobility behavior of people, and GPS tracking has evolved into a major tool to investigate tourism mobility behavior. For example, the use of GPS data loggers enables the recording and analysis of routes and time-space movements of participants. Through the combination of research tools, additional data can be collected, such as activities at the Point of Interest (PoI), motivations (e.g., for spending time at a specific PoI), demographic data and visitor satisfaction. An Android Application for tablets developed by the Harz University allows the link between complementary data-collection tools: GPS tracking and face-to-face surveys. The software GimToP (GTK) enables the researcher to collect data in-situ, and subsequently displays specific results (e.g., track, distance, breaks) in an interactive map. This way, respondents can be asked to provide data during their experience at various track points, which represents a new and significant tool to understand the mobility and space-time behavior of a variety of respondent groups, such as hikers, city tourists, as well as visitors of leisure facilities or tourist attractions. This presentation will introduce the most important goals and opportunities of this new software, underpinned by a case study presenting the used GTK for hikers in the Harz Mountains.